On the Nature and Origin of Bipolar Electrostatic Structures in the Earth's Bow Shock - Vasko, Ivan Y.; Wang, Rachel; Mozer, Forrest S.; Bale, Stuart D.; Artemyev, Anton V. (Frontiers in Physics, 2020)
We present a statistical analysis of large-amplitude bipolar electrostatic structures measured by the Magnetospheric Multiscale spacecraft in the Earth's bow shock. The analysis is based on 371 large-amplitude bipolar structures collected in nine supercritical quasi-perpendicular Earth's bow shock crossings. We have found that 361 of the bipolar structures have negative electrostatic potentials, and only 10 structures (<3%) have positive potentials. The bipolar structures with negative potentials are interpreted in terms of ion phase space holes produced by ion streaming instabilities and, particularly, by the two-stream instability between incoming and reflected ions. We have obtained the upper estimate for amplitudes of the ion phase space holes that is in agreement with the measurements. The bipolar structures with positive potentials might be electron phase space holes produced by electron two-stream instabilities. We argue that the negligible amount of electron phase space holes among large-amplitude bipolar structures is due to the electron hole transverse instability, which criterion is highly restrictive at omega_pe/omega_ce>> 1, a parameter range typical of collisionless shocks in the heliosphere and various astrophysical environments. This analysis indicates that the original mechanism of electron surfing acceleration involving electron phase space holes is not likely to be efficient in realistic collisionless shocks.